Minat Beli Hijau: Dampak Attitude Towards Green Brand dan Green Brand Knowledge pada Produk Danone Indonesia - Arkan Ranggadipta; Kristina Sisilia (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to determine the role of green brand knowledge as a moderator between attitude towards green brand products of Pt Danone Indonesia and consumers' green buying interest. This study used a non-probability sampling method with purposive sampling and a Likert scale for quantitative analysis. People who live in Greater Bandung and know that Danone products are environmentally friendly brands make up a sample size of 152. Green brand knowledge has a positive and significant effect on attitude towards green brand, with a t-value of 51.009 > p-value of 1.649.